Markets and Medicine : the Politics of Health Care Reform in Britain, Germany, and the United States. (University of Michigan Press, 2009)
Are advanced industrialized countries converging on a market response to reform their systems of social protection? By comparing the health care reform experiences of Britain, Germany, and the United States in the 1990s, Susan Giaimo explores how countries pursue diverse policy responses and how such variations reflect distinctive institutions, actors, and reform politics in each country. In Britain, the Thatcher government's plan to inject a market into the state-administered national health service resulted in a circumscribed experiment orchestrated from above. In Germany, the Kohl government sought to repair defects in the corporatist arrangement with doctors and insurers, thus limiting the market experiment and designing it to enhance the solidarity of the national health insurance system. In the United States, private market actors foiled Clinton's bid to expand the federal government's role in the private health care system through managed competition and national insurance. But market reform continued, albeit led by private employers and with government officials playing a reactive role. Actors and institutions surrounding the existing health care settlement in each country created particular reform politics that either militated against or fostered the deployment of competition. The finding that major transformations are occurring in private as well as public systems of social protection suggests that studies of social policy change expand their focus beyond statutory welfare state programs. The book will interest political scientists and policymakers concerned with welfare state reform in advanced industrial societies; social scientists interested in the changing balance among state, market, and societal interests in governance; and health policy researchers, health policymakers, and health care professionals. Susan Giaimo is an independent scholar. She completed her Ph. D. in Political Science at the University of Wisconsin-Madison. She also earned an MSc in Politics from the London School of Economics and Political Science, with the Politics and Government of Western Europe as the branch of study. After completing her doctorate, she was a postdoctoral fellow in the Robert Wood Johnson Foundation Scholars in Health Policy Research Program, University of California at Berkeley, and the Robert Bosch Foundation Scholars Program in Comparative Public Policy and Comparative Institutions, American Institute for Contemporary German Studies, Johns Hopkins University. She taught in the Political Science Department at Massachusetts Institute of Technology for five years. During that period she won the Society for the Advancement of Socio-Economics Founder's Prize for "Adapting the Welfare State: The Case of Health Care Reform in Britain, Germany, and the United States," a paper she coauthored with Philip Manow. She has also worked for health maintenance organizations (HMOs) and medical practices in the United States.